2017
DOI: 10.1002/anie.201706684
|View full text |Cite
|
Sign up to set email alerts
|

Photosalient Phenomena that Mimic Impatiens Are Observed in Hollow Crystals of Diarylethene with a Perfluorocyclohexene Ring

Abstract: A diarylethene with a perfluorocyclohexene ring formed hollow crystals by sublimation under normal pressure. Upon UV irradiation of the crystals, they showed remarkable photosalient phenomena and scattered into small pieces. The speed of the flying debris released from the crystal by UV irradiation exceeded several meters per second. To clearly show a photosalient effect resembling the scattering behavior of Impatiens on a smaller scale, small fluorescent beads (1-μm diameter) were inserted into the hollow cry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
59
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(61 citation statements)
references
References 32 publications
2
59
0
Order By: Relevance
“…[3] Such materials would combine the molecular order of single crystals with the properties of soft matter. [4] Av ariety of crystalline materials that display stimuliresponsive behaviour, [5] including breathable metal-organic frameworks, [6] spin-crossover materials, [7] thermosalience, [8] mechanosalience, [9] and photosalience [10] have been reported along with examples of both plastically [11] and elastically flexible crystals. [3a,8b, 12] Often, the fundamental mechanisms that lead to this behaviour are not well understood [11d,13] even though such materials may have applications in diverse areas from precision engineering to flexible electronics.…”
mentioning
confidence: 99%
“…[3] Such materials would combine the molecular order of single crystals with the properties of soft matter. [4] Av ariety of crystalline materials that display stimuliresponsive behaviour, [5] including breathable metal-organic frameworks, [6] spin-crossover materials, [7] thermosalience, [8] mechanosalience, [9] and photosalience [10] have been reported along with examples of both plastically [11] and elastically flexible crystals. [3a,8b, 12] Often, the fundamental mechanisms that lead to this behaviour are not well understood [11d,13] even though such materials may have applications in diverse areas from precision engineering to flexible electronics.…”
mentioning
confidence: 99%
“…Locking the crystal through the introduction of supramolecular hydrogen‐bonding urethane motifs causes mechanical stress to build‐up upon UV light irradiation that results in the crystals “exploding” after accumulating enough stress . This rare phenomenon, termed the “photosalient effect,” could also be shown in the case of remarkable hollow‐shaped crystals of a DAE with the classical perfluorocyclohexene bridge, while single‐wall crystals of the same molecule experienced photoinduced bending . The intensity as well as the direction of incident light affect the resulting motion, for example, stepwise irradiation triggered delayed motion in certain DAE crystals, whereas irradiating a crystal with two different wavelengths of UV light triggered the crystal to move in two different directions.…”
Section: Crystalline Photoswitchable Materialsmentioning
confidence: 99%
“…Uchida and Morimoto et al. reported a hollow crystal of diarylethene (Figure a, b, and e) that displayed a remarkable photosalient phenomenon . Interestingly, it was observed that the flying debris released from the crystal exceeded several meters per second upon UV irradiation.…”
Section: Classification Of Photomechanical Organic Crystals Based On mentioning
confidence: 99%